Sosialisasi Pengolahan Sampah Organik Menjadi Pupuk Kompos di Desa Jelantik Kabupaten Lombok Tengah - Hasyim; Saidah, Humairo; Sideman, Ida Ayu Oka Suwati; Budianto, Muh. Bagus; Widianty, Desi; Karyawan, Dewa Made Alit; Negara, I Dewa Gede Jaya; Seniari, Ni Made (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
Jelantik Village faces environmental problems, especially waste generation from agricultural and household activities. The main livelihood of the people of Jelantik Village is livestock and farming. Because farming is the main livelihood, the people of Jelantik Village really need fertilizer for their agricultural needs, so it is very profitable if they are able to process organic waste into fertilizer. However, the people of Jelantik do not yet understand how to use waste to make fertilizer. This activity aims to help the people of Jelantik Village understand how to process waste, especially organic waste from agriculture, livestock, the tofu and tempeh industry, and household waste, into useful compost. The socialization was carried out using counselling methods and the direct practice of making compost using straw and an EM4 activator. The counselling was attended by at least 25 participants in a warm atmosphere and without any difficulties. The team has been able to share knowledge with the Jelantik Village community about the principles and stages of making proper compost fertilizer, so it is hoped that this can reduce the waste problem while producing quality compost fertilizer.